MANGALIA SPAS POTENTIAL, A POTENTIAL TOURISM RESOURCE OF THE ROMANIAN SEASIDE - Daniela-Mirela PLEȘOIANU; Iulia EFTEI (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
Treatment Tourism is a specific form of rest tourism, destined to prevent certain illnesses or diseases. This is one form of the constant movement of a tourist relatively stable clientele. The paper analyzes the main forms of tourism in the area, referring in particular to the spa potential and its recovery. The study analyzes the main forms of tourism in Mangalia, focusing on spa treatment and the resources available in the city for bathing cures. The data from the National Institute of Statistics, Department of Statistics Constanta, regarding the flow of tourists in Mangalia were used. The data were processed and converted into tables, graphs and then analyzed and interpreted. The study pointed out that Mangalia is visited by tourists four months a year (June, July, August, and September), and tourists who spent their holidays in Mangalia are both of Romanian and foreign origin. The number of tourists in Mangalia fluctuated from 210,000 in 2010 to 240,000 in 2014. The average length of stay is 5 days in sanatorium, like in the rest of spas in the country. Of the total arrivals in Mangalia, only 2% tourists have treatment tickets. Customer categories have the following structure: 35% retired persons, 25% people with secondary education, 25% persons with higher education, 5% artists and sportsmen, 0.5% other professions.